Evaluation of Hydrothermal Treatment of Empty Fruit Bunch for Solid Fuel and Liquid Organic Fertilizer Co-Production. (November 2015) - Nurdiawati, Anissa; Novianti, Srikandi; Zaini, Ilman Nuran; Nakhshinieva, Bakhtiyor; Sumida, Hiroaki; Takahashi, Fumitake; Yoshikawa, Kunio
Abstract: The hydrothermal treatment (HT) has demonstrated the ability to improve fuel characteristics of biomass. On the other hand, the liquid by-product, which potentially contains solubilized nutrient, is being poorly utilized. This paper presents an investigation on HT of empty fruit bunch (EFB) on both solid and liquid product characteristics. In this work, the effects of HT on EFB were investigated at the HT temperatures of 100, 150, 180 and 220 °C with the holding time of 30 minutes. The results showed that HT can increase the carbon content, remove up to 55% of ash content from EFB, lowering the potassium and chlorine contents down to 0.84% and 0.18%, respectively. Moreover, maximum of 37% of nitrogen, 65% of potassium and less than 10% of phosphorus in EFB were dissolved into the liquid product which positively correlated with the HT temperature. These results demonstrate the possibility of employing HT for producing solid fuel as well as nutrient recovery from EFB.